Inibindo a decoerência de memórias quânticas em cavidades de microondas realísticas - Jose Geraldo Goncalves de Oliveira Junior (2006)
In this work we study the dynamics of the atomfield interaction in a realistic optical cavity and we describe typical experiments in cavity quantum electrodynamics. Afterwards, we establish a procedure to control the holding time of a quantum memory in a cavity with high quality factor, using the ideas of J. G. Peixoto de Faria, P. Nussenzveig, A. F. R. de Toledo Piza & M. C. Nemes, Los Alamos eprint server, xxx.lang.gov/quantph/0012037 about increasing the decay time of a single photon state. Moreover, we analyze effects that contribute to the reduction of the holding time during experiments.